The mosquito effect: regulatory and effector T cells acquire cytoplasmic material from tumor cells through intercellular transfer - Hioki, Kaito A.; Ryan, Daniel J.; Thesmar, Iris; Lynch, Adam C.; Pobezinsky, Leonid A.; Pobezinskaya, Elena L. (Frontiers in Immunology, 2023)
The phenomenon of intercellular transfer of cellular material, including membranes, cytoplasm, and even organelles, has been observed for decades. The functional impact and molecular mechanisms of such transfer in the immune system remain largely elusive due to the absence of a robust in vivo model. Here, we introduce a new tumor mouse model, where tumor cells express the soluble ultra-bright fluorescent protein ZsGreen, which allows detection and measurement of intercellular transfer of cytoplasm from tumor cells to infiltrating immune cells. We found that in addition to various types of myeloid lineage cells, a large fraction of T regulatory cells and effector CD8 T cells acquire tumor material. Based on the distribution of tumor-derived ZsGreen, the majority of T cells integrate captured cytoplasm into their own, while most myeloid cells store tumor material in granules. Furthermore, scRNA-seq analysis revealed significant alterations in transcriptomes of T cells that acquired tumor cell cytoplasm, suggesting potential impact on T cell function. We identified that the participation of T cells in intercellular transfer requires cell-cell contact and is strictly dependent on the activation status of T lymphocytes. Finally, we propose to name the described phenomenon of intercellular transfer for tumor infiltrating T cells the "mosquito effect".